2023
DOI: 10.1037/adb0000859
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional prospective associations between behavioral economic indicators and drinking patterns during alcohol use disorder natural recovery attempts.

Abstract: Objectives: Behavioral economic (BE) theory posits that harmful alcohol use is a joint product of elevated alcohol demand and preference for immediate over delayed rewards. Despite cross-sectional research support, whether expected bidirectional relations exist between BE indicators and drinking during recovery attempts is unknown. Therefore, this prospective research investigated quarter-by-quarter cross-lagged associations between BE simulation tasks and drinking following a natural recovery attempt. Higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
5
1
Order By: Relevance
“…The present study critically extends a sizeable body of cross‐sectional literature [18,32] and initial longitudinal work [48,49] by providing a robust longitudinal examination of prospective and bidirectional associations between key behavioral economic indicators and alcohol‐related outcomes among a relatively large sample of emerging adults. The results revealed several relationships that were consistent with behavioral economic predictions [14,15], in addition to others that were less consistent or not supported.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The present study critically extends a sizeable body of cross‐sectional literature [18,32] and initial longitudinal work [48,49] by providing a robust longitudinal examination of prospective and bidirectional associations between key behavioral economic indicators and alcohol‐related outcomes among a relatively large sample of emerging adults. The results revealed several relationships that were consistent with behavioral economic predictions [14,15], in addition to others that were less consistent or not supported.…”
Section: Discussionmentioning
confidence: 77%
“…The present study critically extends a sizeable body of cross-sectional literature [18,32] and initial longitudinal work [48,49] by providing a robust longitudinal examination of prospective and bidirectional associations between key behavioral economic indicators and alcoholrelated outcomes among a relatively large sample of emerging adults.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Gaume et al (2022) found that demand intensity, break point, O max , and sensitivity to changes in alcohol price predicted changes in alcohol use and problems over a 4-year period in a large sample of Swiss men who were 21 years old at baseline. Finally, one prospective study examined cross-lagged bidirectional associations quarter-to-quarter between BE demand and drinking status during the year following initiation of a natural recovery attempt among untreated problem drinkers (Cheong et al, 2023). Higher intensity in Quarter 1 distinguished participants who drank heavily in Quarter 2 from those who abstained.…”
Section: Behavioral Economicsmentioning
confidence: 99%
“…These same relations were soon reported with other substance use disorder populations, including smokers (Bickel et al, 1999) and opiate users (Kirby et al, 1999), and a large literature on temporal discounting and substance use rapidly developed (summarized in Bickel & Marsch, 2001; Koffornus & Kaplan, 2018; Madden & Bickel, 2010). Discounting tasks robustly differentiate substance use groups defined by problem severity in cross‐sectional research, but their predictive utility has not been well established in longitudinal research (Cheong et al, 2022; de Wit & Mitchell, 2010).…”
Section: Human Laboratory Studies Of Temporal Discounting and Economi...mentioning
confidence: 99%